Computers and technology in a changing society - Morley, Deborah (Thomson/Course Technology, 2006)
There are few ways in which computers and technology don't impact our lives on a daily basis. As result, it is increasingly important that students are not only fluent in the many ways that technology can benefit them, but are also aware of the effects it has on society. Computers and Technology in a Changing Society, Second Edition is a unique text that provides a concise introduction to the computer concepts that students need to know, as well as the risks and issues that accompany their use